Early pubertal timing is common among adolescent girl-to-boy sex reassignment applicants. (1st November 2016) - Sumia, Maria; Lindberg, Nina; Työläjärvi, Marja; Kaltiala-Heino, Riittakerttu
Abstract: Objectives: The aim of our study was to explore whether gender dysphoria in adolescent girls is associated with early pubertal timing. Methods: We compared menarcheal timing among 52 adolescent girl-to-boy sex reassignment (SR) applicants with that of 644 adolescent girls who participated in an adolescent population mental health survey. Results: Of the population girls, 21% presented with early (≤11 years), 61% with normative (12–13 years) and 19% with late (≥14 years) menarcheal timing; among the SR applicants, 42% presented with early, 46% with normative and 12% with late menarcheal timing ( p = 0.003). The odds ratio for SR applicant girls to have early menarcheal timing was 2.7 (95% confidence interval (CI) 1.3, 5.7), controlling for age and family structure. Conclusion: Like emotional and behavioural disorders, gender dysphoria in adolescence is associated in girls with early pubertal timing. The finding is discussed in the light of literature related to pubertal maturation and mental health.